1990
DOI: 10.1073/pnas.87.17.6584
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 2 receptor beta chain expressed in an oligodendroglioma line binds interleukin 2 and delivers growth signal.

Abstract: Interleukin 2 (IL-2) is a potent growth factor for T lymphocytes, playing a crucial role in the immune response. In view of the considerable evidence that the immunoregulatory cytokines (or lymphokines) also play a role in the growth and differentiation of cells in the central nervous system (CNS), we examined the operation of the IL-2 system in a cell line of CNS origin by expressing a cDNA encoding the (3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1991
1991
1997
1997

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 34 publications
(29 reference statements)
0
13
0
Order By: Relevance
“…The mouse IL-3-dependent pro-B-cell line BAF-B03 (8) and its derivatives were maintained in RPMI 1640 medium supplemented with 10% fetal calf serum and 20%o WEHI-3B conditioned medium (as a source of IL-3). BAF-B03 was stably transfected with the expression vector for the human IL-2R3, pEF/,3 (23), along with a neomycin-resistant gene by the electroporation method. After DNA transfer, neomycinresistant clones were selected as described (9).…”
Section: Methodsmentioning
confidence: 99%
“…The mouse IL-3-dependent pro-B-cell line BAF-B03 (8) and its derivatives were maintained in RPMI 1640 medium supplemented with 10% fetal calf serum and 20%o WEHI-3B conditioned medium (as a source of IL-3). BAF-B03 was stably transfected with the expression vector for the human IL-2R3, pEF/,3 (23), along with a neomycin-resistant gene by the electroporation method. After DNA transfer, neomycinresistant clones were selected as described (9).…”
Section: Methodsmentioning
confidence: 99%
“…IL-2R is composed of at least two subunits, the ~ (p55) and/3 (p75) chains. IL-2Rfl but not IL-2Rot has been shown to be a molecule responsible for transduction of growth signals when expressed on lymphoid and oligodendroglioma cells [2,3]. Recent studies using IL-2R~ and -/3 cDNA-transfected fibreblast cell lines have shown thai the cz and ~ subunits are not enough to forna the high affinity functional IL-2 receptor [4].…”
Section: Introduction Interleukin 2 (Il-2) Is a Well-characterized Lymentioning
confidence: 99%
“…EcoRI-digested PCR products were cloned into the Bluescript at EcoRI site, and the sequence of the respective PCR products was confirmed. Subsequently, the cDNA fragments for DnrkS and DnrkL with EcoRI sites were ligated to the EcoRI-cleaved backbone fragment of the pEF expression vector (29), with an additional nucleotide sequence that encodes the two tandemly repeated HA epitopes, at the 5Ј end of the EcoRI-cleaved vector.…”
Section: Methodsmentioning
confidence: 99%